THE EFFECT OF THINK PAIR SHARE TECHNIQUE ON THE ABILITY OF THE FIRST YEAR STUDENTS OF MADRASAH ALIYAH DARUL HIKMAH PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Siti Aminah; Eliwarti Eliwarti; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed at finding out whether there is significant effect of using TPS (Think –Pair- Share) technique on the students ability of the first year students of Madrasah Aliyah Darul Hikmah Pekanbaru in comprehending narrative texts. The design of the research is pre-experimental. The population and sample are the first grade student of Madrsah Aliyah Darul Hikmah Pekanbaru. The number of sample is selected by using cluster random sampling technique. To get the data, the researcher conducted a pre-test and a post-test, then the results are analyzed using quantitative data calculated by SPSS 16 version. The result of sig. value is 0.000. It can be stated that 0.000 < 0.005. Then, the result of t-test is 14. 82, meanwhile t-table is 1.701. The t-test is higher than the t-table. It means that Hypothesis is accepted. In other words, there is a significant effect of using TPS (Think-Pair-Share) technique on the students ability of the first year students of Madrasah Aliyah Darul Hikmah Pekanbaru in comprehending narrative texts.Key words: TPS(Thnik-Pair-Share), technique, reading comprehension, narrative text.